Evaluation of the Q Method as a Public Engagement Tool in Examining the Preferences of Residents in Metal Mining Areas - Sardo, Ana Margarida; Sinnett, Danielle (Frontiers in Communication, 2020)
IIn this study, we describe and present an evaluation of how the Q Method was used to engage members of local communities, to examine how those living in former metal mining landscapes value their heritage and understand their preferences for the long-term management of mine waste. The evaluation focused on the participants’ experiences, thoughts, and views of the Q Method, as a method of collecting individual preferences. The Q Method is for discourse analysis, allowing a systematic analysis of the subjective perspectives of participants. This paper presents a small-scale evaluation of the Q Method. The results indicate that although this method is time-consuming (both for the researchers and for the participants) and demanding, it is a suitable and successful engagement strategy. The Q Method helped the participants feel that their opinion was being sought and valued, and allowed them to express their views on mining heritage in the context of their lives. The method was also a valuable tool in challenging the participants’ views and it reinforced the complexity of the decision-making process.